Pengaruh Terpaan Media dan Sosialisasi Politik melalui Primary Groups terhadap Proses Pengambilan Keputusan Pemilih - Febri Nurrahmi (Jurnal Komunikasi Global, 2017)
This study aims to see the effect of political information obtained from mass communication and interpersonal communication to the voters’ quality of decision-making process in the 2009 Presidential Election. This study examines the causal relationship between five variables, namely media exposure, political socialization through primary groups, political engagement, central route, and peripheral route. The problem formulation is constructed based on the Elaboration Likelihood Model (ELM) assumptions adapted to the electoral context. This study used cross-sectional survey towards 201 urban voters of Beji Sub-district who were selected randomly using multistage random sampling techniques. Data analysis techniques are univariate analysis with SPSS 17.0 and multivariate analysis with One-Step Approach Structural Equation Modeling (SEM) method using Lisrel 8.71. The results show that the majority of voters in the 2009 presidential election used the irrational processing of political information through peripheral route. The study also shows that media exposure and political socialization through primary groups can be acted as antecedent variables to the correlational relationship between political engagement and political information processing.